Motivasi Wisatawan Dalam Pembelajaran Yoga Di Ubud Bali - I Wayan Suyanta (Jayapangus Press, 2021)
This research is aimed at the motivation to learn yoga by tourists visiting Ubud Bali. By observing the symptoms of fragility and independence of internal and external elements of tourists along with the situation and conditions in the West, it is necessary to identify motives and find solutions to the problems. Tourists' learning motives will be explored and explored from the perspective of non-formal education. The method used is deepth interview, which continues to be described in a qualitative descriptive manner. Some of the findings include the stimulation of the external environment in the Western world and personality situations that cause tourists to start learning yoga. Another motive is the awareness of tourists' self-introspection, edu-spiritual learning (non-formal education) and the Balinese social and cultural environment as an orientation to learn yoga.